Hadiyah-ʼi Nawrūz (Kumītah-ʼi Farhangī-i Jamʻīyat-i Islāmī-i Afghānistān : Āmrīyat-i Nasharāt-i Idārah-i Jarīdah-i Mujāhid, 1987)
Poems by contemporary Afghan poets on destruction of their country by Russians.